National Decision Making and Nuclear Fuel Cycles: An Analysis of Influences. - Platte, James. (2017)
Abstract: This study examines the factors that influence national decisions about developing nuclear fuel cycle technology, and the central question for this study is why countries have developed different national nuclear fuel cycles. Prospect theory is used as the basis of an analytical framework for studying nuclear fuel cycle decision making. In essence, prospect theory states that nations are risk averse when in a gains domain and risk acceptant when in a losses domain. This study hypothesizes that a country's nuclear fuel cycle decision making is determined by the frame of reference and domain (either gains or losses) and that security concerns are a factor driving policy behind all nuclear programs. A structured, focused comparison of Indian, Japanese, and South Korean nuclear fuel cycle decision making was conducted in order to test the hypotheses. Major nuclear fuel cycle decisions made between approximately 1950 and 1990 in each country were analyzed. The results verified this study's hypotheses. Decisions were mostly made according to the tenets of prospect theory, and security concerns (national security or energy security) were a driver for the nuclear programs in all three countries. The study also emphasized that nuclear fuel cycle technology is strategic and highly valued by countries and that national leaders are involved with making major nuclear fuel cycle decisions. Prospect theory proved to be a more powerful analytical tool than existing theories of nuclear weapons proliferation. Prospect theory accounts for a country's capabilities, intentions, and situational and temporal context. In this way, prospect theory gives a holistic view of how all nuclear technologies fit into strategic interests and how a country's leadership's frame of reference with regard to strategic interests influences the direction of nuclear fuel cycle decision making. Prospect theory on its own does not offer a model or predictor of nuclear fuel cycle technology development, but it illuminates how leaders viewed nuclear fuel cycle decisions and why certain decisions were made.; Thesis (Ph.D.)--Tufts University, 2013.; Submitted to the Dept. of Diplomacy, History, and Politics.; Advisor: William Martel.; Committee: William Moomaw, and Robert Pfaltzgraff.; Keyword: International relations.